2000
DOI: 10.1088/0953-4075/33/17/309
|View full text |Cite
|
Sign up to set email alerts
|

CIV3 and relativistic quantum defect orbital (RQDO) oscillator strengths in Mg-like ions of astrophysical interest

Abstract: Astrophysically relevant transitions in the Mg-like ions Si III, S V and Fe XV have been studied. A J -dependent CIV3 calculation, more extensive than other, earlier ones, has led to improved accuracy in the calculated energy levels and oscillator strengths. Independent relativistic quantum defect orbital and multiconfigurational Dirac-Fock calculations have also been performed. An analysis of the results is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Interestingly, with a much smaller basis set, level energies for Fe XV from our group (Deb & Msezane 1998;Deb et al 1999) showed far better agreement with the measurement. However, their (Almaraz et al 2000) calculated oscillator strengths using MCDF agree closely with their length form of the CIV3 results as do the recent experimental values. Their RQDO method based on a simple model potential gave reasonably good oscillator strengths for the ions towards the neutral end of the sequence, but poor agreement with the measured data and both their CIV3 and MCDF for the 3s 2 ( 1 S 0 ) → 3s3p( 1 P 1 ) transition in Fe XV.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, with a much smaller basis set, level energies for Fe XV from our group (Deb & Msezane 1998;Deb et al 1999) showed far better agreement with the measurement. However, their (Almaraz et al 2000) calculated oscillator strengths using MCDF agree closely with their length form of the CIV3 results as do the recent experimental values. Their RQDO method based on a simple model potential gave reasonably good oscillator strengths for the ions towards the neutral end of the sequence, but poor agreement with the measured data and both their CIV3 and MCDF for the 3s 2 ( 1 S 0 ) → 3s3p( 1 P 1 ) transition in Fe XV.…”
Section: Introductionsupporting
confidence: 82%
“…Almaraz et al (2000) have performed more extensive CIV3 calculations to study the configuration mixing among the levels involved in the 3s 2 ( 1 S 0 ) → 3snp( 1,3 P 1 ) (n = 3−5) transitions in Mg-like ions such as Si III, S V and Fe XV. They also used relativistic quantum defect orbital (RQDO) formalism and MCDF procedures in their investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Safronova et al (2000) used relativistic second-order many body perturbation theory (MBPT) to calculate excitation energies and transition rates for the same transition arrays. Almaraz et al (2000) applied the CIV3 code (Hibbert 1975) to calculate energy levels and oscillator strengths in Si iii.…”
Section: Previous Work On Atomic Data For Si III and Si Ivmentioning
confidence: 99%
“…The line ratio calculations in turn need accurate determination of atomic data such as energy levels, oscillator strengths, transition probabilities and lifetimes. The calculations of these parameters for a number of allowed and intercombination transitions in Mg-like ions have been previously reported by many workers (Froese Fischer and Godefroid 1982a, 1982b, Fawcett 1983, Tayal 1986, Chou et al 1993, Stanek et al 1996, Jonsson and Froese Fischer 1997, Zou and Froese Fischer 2001, Butler et al 1993, Chen and Cheng 1997, Deb and Msezane 1998, Deb et al 1999, Almaraz et al 2000, Safronova et al 2000, Gupta and Msezane 2000, Biémont et al 2002, Aggarwal et al 2003, Das et al 2004. Most of the available theoretical data in the literature for highly charged Mg-like ions so far are confined to the calculation of energy levels (Ivanova et al 1986).…”
Section: Introductionmentioning
confidence: 97%